Impacto en los ajustes de protección debido a los efectos de acople mutuo en líneas de transmisión con derivaciones (2020)
This document presents an analysis about the effects of mutual coupling on the protection algorithms between the sequence networks of the same circuit and between different circuits in parallel transmission lines, in addition to the effects on parallel transmission lines out of service. Initially, theoretical analyzes on transmission systems are carried out to understand the coupling effect and in this way generate the necessary equations that describe their behavior. Following this, practical analyzes are carried out on predefined models to check the theoretical results and thus give truth to the equations described above. With this, we proceed to analyze the effects of coupling on new cases that are more present on an electrical system, from which new configuration guidelines are obtained for the protection algorithm in these cases. Finally, a discussion is generated about the results obtained throughout the project and the general configuration guidelines are generated for each of the cases analyzed, revealing the importance of the coupling effect in transmission systems and the importance of the configurations. for each case.